Synergic impact of oral anticoagulation control and renal function in determining major adverse events in atrial fibrillation patients undergoing percutaneous coronary intervention: insights from the AFCAS registry - Proietti Marco; Airaksinen K E Juhani; Rubboli Andrea; Schlitt Axel; Kiviniemi Tuomas; Karjalainen Pasi P; Lip Gregory Y H (SPRINGER HEIDELBERG, 2022)
In patients with atrial fibrillation (AF), quality of oral anticoagulation control as well as impaired renal function are associated with adverse outcomes. Our objective was to analyze if there was a synergistic impact of these factors in determining adverse outcomes in AF patients undergoing percutaneous coronary intervention and stent (PCI-S).Post-hoc analysis from the Atrial Fibrillation Undergoing Coronary Artery Stenting (AFCAS) registry. Poor oral anticoagulation control was defined as time in therapeutic range (TTR) < 65%, while impaired renal function as creatinine clearance (CrCl) < 60 ml/min.Of the whole cohort, 448 were eligible for this post-hoc analysis. Of these, 27.9% had TTR < 65%only (Group I), 19.2% had CrCl < 60 ml/min only (Group II), while 13.8% had both conditions (Group III). At follow-up, patients in Group III had a higher rate of major adverse cardiovascular and cerebrovascular events (MACCE) (p = 0.007), while patients in Groups I and III had higher rates of major bleeding. Kaplan-Meier analyses showed that patients in Group III had higher risk for MACCE (LogRank: 14.406, p = 0.003), while Group I and Group III patients had higher risk for major bleeding (LogRank: 12.290, p = 0.006). On Cox regression, presence of both conditions independently increased MACCE risk (p = 0.001), while TTR < 65% alone and the presence of both conditions were independently associated with major bleeding (p = 0.004 and p = 0.028, respectively).There was a synergic impact of oral anticoagulation control and renal function in determining major adverse events in AF patients undergoing PCI-S. Use of poor anticoagulation control and impaired renal function in combination would help identify AF patients undergoing PCI-S at risk for MACCE and/or major bleeding.